Предмет: Математика, автор: vitekgorlov

Помогите, пожалуйста.
Заранее спасибо, с Новым Годом Вас и Рождеством!

Приложения:

Ответы

Автор ответа: Удачник66
0

Ответ:

Пошаговое объяснение:

а) y=\frac{13}{7x^7-12^5+x}

y'=\frac{-13(7*7x^6-12*5x^4+1)}{(7x^7-12x^5+x)^2} =-\frac{13(49x^6-60x^4+1)}{(7x^7-12x^5+x)^2}

б) y=ln(5x+cos(x))

y'=\frac{5-sin(x)}{5x+cos(x)}

в) y=\frac{-8x^2+x-4x^5}{\sqrt{x^2-7} }

y'=\frac{(-16x+1-20x^4)\sqrt{x^2-7} -(-8x^2+x-4x^5)*2x/(2\sqrt{x^2-7} )}{x^2-7}=

=\frac{(-16x+1-20x^4)(x^2-7)-x(-8x^2+x-4x^5)}{x^2-7} =\frac{(-16x+1-20x^4)(x^2-7)+(8x^3-x^2+4x^6)}{x^2-7}

Похожие вопросы